[1908 women's basketball team] - Frank Aston::::::photographer::: (1908)
1908 women's basketball team in uniform; with coach Margaret Chase; on outdoor court. (Published with all members identified in caption in Polytechnic J. (v.4, no. 5, Feb. 1909)